2019
DOI: 10.4251/wjgo.v11.i8.642
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of lymphatic and blood vessel invasion and Borrmann types in advanced proximal gastric cancer

Abstract: BACKGROUND The Borrmann classification system is used to describe the macroscopic appearance of advanced gastric cancer, and Borrmann type IV disease is independently associated with a poor prognosis. AIM To evaluate the prognostic significance of lymphatic and/or blood vessel invasion (LBVI) combined with the Borrmann type in advanced proximal gastric cancer (APGC). METHODS The clinicopathological and survival data of 440 patients with APGC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
(18 reference statements)
1
4
0
2
Order By: Relevance
“…Yamashita et al [ 23 ] considered that for patients with pTNM stage II/III, giant Borrmann type III AGC (≥8 cm) had similar sensitivity to postoperative adjuvant chemotherapy with Borrmann type IV AGC; Both belonged to the high-risk macroscopic type, and the 5-year survival rate was 35.7%. However, other studies found that patients with vascular infiltration Borrmann type III had the same poor prognosis as type IV, with a 5-year survival rate of 16.4%–19.4% [ 8 , 24 ]. The reason for this divergence is the high heterogeneity of GC.…”
Section: Discussionmentioning
confidence: 99%
“…Yamashita et al [ 23 ] considered that for patients with pTNM stage II/III, giant Borrmann type III AGC (≥8 cm) had similar sensitivity to postoperative adjuvant chemotherapy with Borrmann type IV AGC; Both belonged to the high-risk macroscopic type, and the 5-year survival rate was 35.7%. However, other studies found that patients with vascular infiltration Borrmann type III had the same poor prognosis as type IV, with a 5-year survival rate of 16.4%–19.4% [ 8 , 24 ]. The reason for this divergence is the high heterogeneity of GC.…”
Section: Discussionmentioning
confidence: 99%
“…Since proximal GC has more aggressive biological characteristics than distal GC, the prognosis of proximal GC is worse than that of distant GC[ 20 - 22 ]. The study by Gao et al[ 23 ] showed that in proximal GC, there is no significant difference in prognosis between patients with Borrmann type III disease and LBVI (+) and those with Borrmann type IV and LBVI (-). This is similar to the results of this study, which also included patients with GC in various locations.…”
Section: Discussionmentioning
confidence: 99%
“…When assessing LVI, it is important to exclude false-positive and false-negative cases of LVI, which is possible when using the immunohistochemical method of staining tumor tissue[ 171 ]. In a group of patients with LVI+/perineural invasion (PNI)+, the overall and relapse-free survival rates were significantly lower than in the group of patients who were LVI-/PNI-[ 137 - 140 ], including in patients with lymph node-negative GC[ 141 , 142 ] and in patients who received neoadjuvant chemotherapy[ 172 ]. Interestingly, adjuvant chemotherapy significantly improved overall and disease-free survival in PNI+ but not PNI- patients, and these results were not influenced by disease stage[ 173 ].…”
Section: Results Of Angiogenesis Activity Assessment In Gcmentioning
confidence: 99%